Effects of professional development on the quality of teaching: Results from a randomised controlled trial of Quality Teaching Rounds. (November 2017) - Gore, Jennifer; Lloyd, Adam; Smith, Maxwell; Bowe, Julie; Ellis, Hywel; Lubans, David
Abstract: Robust evidence of the effectiveness of professional development for teachers is limited. This study tested a pedagogy-based, collaborative PD approach for impact on the quality of teaching. A cluster randomised controlled trial involving eight teachers at each of 24 schools found significant positive effects on teaching quality ( d  = 0.4), independent of school type (primary/secondary), school location (urban/rural), and years of teaching experience. These effects were sustained six months later. Qualitative data are used to illustrate mechanisms underpinning the success of the intervention. This study illuminates how to support teacher learning for measurable positive impacts on teaching quality and teacher morale. Highlights: This study tested a pedagogy-based PD approach for impact on quality of teaching. The cluster randomised controlled trial involved 192 teachers in 24 schools. Significant positive effects ( d  = 0.4) were found for teaching quality. Positive impacts on teacher morale and sense of recognition were also observed. Effects were sustained 6 months post-intervention.